Federalism in Nigeria: Between Constitutional Design and Political Reality - Tope Oke Bakare; Tope Shola Akinyetun (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia, 2026)
Federalism in Nigeria, though constitutionally enshrined, has been persistently undermined by structural, political, and socio-economic challenges. Nigeria is a complex country with intriguing multiethnic, multi-religious, and multi-linguistic interests. The heterogeneous nature of Nigeria’s composition makes federalism an appropriate system of government, hence its adoption in 1954. Federalism allows for power sharing between various levels of government, for instance, between the federal or central government and several constituent units (as may exist). Despite the advantages of federalism, its operation has become contentious over the years, casting doubts on its applicability in the Nigerian political context. Rather than advancing national cohesion, federalism in Nigeria has been hindered by challenges such as the over-centralisation of political power, poor leadership, corruption, and bad governance, recurring ethno-religious conflicts, resource control and fiscal operations, revenue allocation, and secession, among others. It is in light of this that this paper - adopting a descriptive approach and relying secondary data - seeks to assess the issues associated with federalism in Nigeria, with its attendant effect. Anchoring the paper on the theory of Classical Model Federalism as postulated by Wheare, it is concluded that the principles of coordination, independence, and autonomy dictated by Wheare’s theory are not adhered to in Nigeria. As a result, it is recommended that the government make sincere efforts to ensure an equitable and even distribution of resources among the federating units in Nigeria, rather than paying lip service to restructuring. The government should declare it a national emergency.